1994
DOI: 10.1007/bf01306455
|View full text |Cite
|
Sign up to set email alerts
|

Mutant herpes simplex virus induced regression of tumors growing in immunocompetent rats

Abstract: Herpes simplex virus (HSV) mutants kill dividing tumor cells but spare non-proliferating, healthy brain tissue and may be useful in developing new treatment strategies for malignant brain tumors. Two HSV mutants, a thymidine kinase deficient virus (TK-) and a ribonucleotide reductase mutant (RR-), killed 7/7 human tumor cell lines in tissue culture. The TK-HSV killed Rat RG2 glioma and W256 carcinoma lines but not the rat C6 glioma in culture. TK-HSV replication (12 pfu/cell) was similar to wild-type HSV (10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Several groups have demonstrated that mice inoculated intracranially with either syngeneic or xenogeneic glioma cells exhibit enhanced survival if the glioma implants are challenged by HSV infection (1,4,7,17,18,24,27,28,29,35). While animals in initial experiments succumbed to encephalitis due to extensive lytic growth of the virus, later studies were thwarted by viruses that were overattenuated due to mutation of the ␥34.5 gene, causing the animals to die from regrowth of the tumor.…”
Section: Vol 11 2001mentioning
confidence: 99%
“…Several groups have demonstrated that mice inoculated intracranially with either syngeneic or xenogeneic glioma cells exhibit enhanced survival if the glioma implants are challenged by HSV infection (1,4,7,17,18,24,27,28,29,35). While animals in initial experiments succumbed to encephalitis due to extensive lytic growth of the virus, later studies were thwarted by viruses that were overattenuated due to mutation of the ␥34.5 gene, causing the animals to die from regrowth of the tumor.…”
Section: Vol 11 2001mentioning
confidence: 99%
“…Intraneoplastic administration of the TK-deleted strains induced tumor regression in several animal tumor models, with severe necrosis of the tumor tissue. [130][131][132][133][134] However, in tumor models in severe combined immunodeficient (SCID) mice, these mutants were shown to spread into normal tissues, 135 indicating a lack of tumor specificity. This, along with concerns that lack of TK would render these mutants insensitive to treatment with the anti-viral drug ACV, has led to the development of many other replication-conditional HSV-1 vectors.…”
Section: Single Gene Deletionmentioning
confidence: 99%
“…The reasons for inserting the transgene into the tk locus include: easy selection of recombinant tk − mutants with the aid of ganciclovir, HSVtk − mutants grow poorly in nondividing cells 24,54,55 and have reduced neurovirulence. 33,56 Replication of HSVtk − mutants in mouse liver was reported to be much less than wild-type HSV, except after partial hepatectomy when liver cells are replicating.…”
Section: Analysis Of Variance Followed By Schaffe's Analysis Was Perfmentioning
confidence: 99%